Governing new global health-care markets: the case of stem cell treatments. Issue 1 (2nd January 2017) - Salter, Brian; Zhou, Yinhua; Datta, Saheli
ABSTRACT: Stem cell innovation has enabled the growth of a global market of treatments for a wide range of diseases but most of this market operates outside the domain of orthodox forms of innovation governance. Much of the analysis of this issue has adopted a supply side perspective informed by the values of the orthodox scientific model of biomedical innovation, arguing that national and transnational regulation has failed to impose appropriate standards on the 'illicit' supply of stem cell treatments. In contrast, this paper shows how and why the analysis of global stem cell innovation governance must incorporate the market and health consumer demand into the conceptual framework. Central to the argument is the role of innovation models in mediating the relationship between demand and supply in the global market of new stem cell treatments. Different models of scientific and medical innovation mediate that relationship in different ways and, in jurisdictions where health consumer demand is frustrated, may result in parallel political demands for change in stem cell innovation governance. Such demands are likely to be resisted by the dominant scientific model, producing a further response from health consumers and a continuing dynamic in the political economy of stem cell treatments.